2018
DOI: 10.1002/anie.201805042
|View full text |Cite
|
Sign up to set email alerts
|

Ultraparamagnetic Cells Formed through Intracellular Oxidation and Chelation of Paramagnetic Iron

Abstract: Making cells magnetic is a long-standing goal of chemical biology, aiming to enable the separation of cells from complex biological samples and their visualization in vivo using magnetic resonance imaging (MRI). Previous efforts towards this goal, focused on engineering cells to biomineralize superparamagnetic or ferromagnetic iron oxides, have been largely unsuccessful due to the stringent required chemical conditions. Here, we introduce an alternative approach to making cells magnetic, focused on biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…[126][127][128][129][130][131] More recently, advances in synthetic biology have made possible the ability to enhance the capabilities of the motile microorganism without the use of artificial components. For example, genetically engineered bacteria have been programmed to generate diverse active components, such as magnetic particles, [132,133] gas-filled microstructures, [134,135] therapeutic payloads, [136] or responsive probes. [137] In a nutshell, locally powered microrobots have built-in energy conversion on their active surfaces or exploited the autonomous motility of microorganisms.…”
Section: Robotics Engines At Small Scalesmentioning
confidence: 99%
“…[126][127][128][129][130][131] More recently, advances in synthetic biology have made possible the ability to enhance the capabilities of the motile microorganism without the use of artificial components. For example, genetically engineered bacteria have been programmed to generate diverse active components, such as magnetic particles, [132,133] gas-filled microstructures, [134,135] therapeutic payloads, [136] or responsive probes. [137] In a nutshell, locally powered microrobots have built-in energy conversion on their active surfaces or exploited the autonomous motility of microorganisms.…”
Section: Robotics Engines At Small Scalesmentioning
confidence: 99%
“…A third approach aimed to magnetize naturally diamagnetic microorganisms or eukaryotic cells by over-expressing iron-storage ferritins or iron-binding proteins inside their cytoplasm. These bacteria could serve as containers favoring the formation of iron-oxide deposits when cells were fed with iron [35][36][37][38][39][40] . These studies showed that mineralized cells contained iron oxide deposits, can be detected using NMR, and can be magnetically sorted.…”
Section: Introductionmentioning
confidence: 99%
“…One second strategy consisted in building bacterial biohybrid systems either using magnetotactic bacteria carrying cargo-particles, , or reciprocally, using a magnetic field to control the orientation of motile bacteria linked to magnetic beads. , A third approach aimed to magnetize naturally diamagnetic microorganisms or eukaryotic cells by overexpressing iron-storage ferritins or iron-binding proteins inside their cytoplasm. These bacteria could serve as containers favoring the formation of iron-oxide deposits when cells were fed with iron. These studies showed that mineralized cells containing iron oxide deposits can be detected using NMR and can be magnetically sorted. However, to envision biotechnological applications using mineralized cells, several important challenges still need to be achieved.…”
mentioning
confidence: 99%
“…A third approach aimed to magnetize naturally diamagnetic microorganisms or eukaryotic cells by over-expressing iron-storage ferritins or iron-binding proteins inside their cytoplasm. These bacteria could serve as containers favoring the formation of iron-oxide deposits when cells were fed with iron [35][36][37][38][39][40] . These studies showed that mineralized cells contained iron oxide deposits, can be detected using NMR, and can be magnetically sorted.…”
Section: Introductionmentioning
confidence: 99%